Post-traumatic Stress Disorder Symptoms and Quality of Life of COVID-19 Survivors at 6-Month Follow-Up: A Cross-Sectional Observational Study - Huang, Liqun; Xu, Xiaohua; Zhang, Lingjie; Zheng, Danwen; Liu, Yuntao; Feng, Bing; Hu, Jiajun; Lin, Qiaoli; Xi, Xiaotu; Wang, Qian; Lin, Meixuan; Zhou, Xin; et al. (Frontiers in Psychiatry, 2022)
Background: PTSD(posttraumatic stress disorder) is the most common psychiatry sequelae among COVID-19. The aim of this study was to determine the prevalence of PTSD symptoms, PTSD-related factors and its relationship with quality of life(QoL) at long-term follow-up in hospitalized COVID-19 survivors. Methods: A cross-sectional study was undertaken to evaluate the health consequences of hospitalized COVID-19 survivors. All participants were interviewed face-to-face with a series of questionnaires such symptom questionnaire, PCL-C(Posttraumatic Stress Disorder Scale Civilian Version), Generalized Anxiety Disorder 7-item, and 36-item Short Form. Results: A total of 574 participants were enrolled with an average age of 57 years. The median follow-up time after discharge was 193.9(SD=15.32) days. 77.9% of survivors presented with at least one symptom, and fatigue or muscle weakness(47.9%) was reported the most frequently, followed by chest distress(29.4%) and sleep difficulty(2.9.4%). The prevalence of PTSD was 11.15%(95%CI: 8.56,13.73) with a cutoff score of 44. Factors like respiratory symptoms(OR: 3.42(95% CI: 1.63-7.18), anxiety symptoms(OR: 15.81, 95% CI: 7.61-32.85) and sleep difficulty(OR: 2.24, 95% CI: 1.18-4.26) were positively related to PTSD. And COVID-19 survivors with potential traumatic stress disorder had significantly lower QoL than those without(P＜0.05). Conclusion: Our study illustrated that a significant number of COVID-19 survivors are suffering from physical or mental distress to varying degrees at 6 months after discharge. And people with PTSD were more subjected to persistent respiratory symptoms, sleep difficulty, as well as anxiety and worse QoL. Such survivors should be paid much more attention to their mental health, especially the PTSD symptoms in early phase, which may play an important role in the recovery of both the physical and psychological health of COVID-19 survivors.